2020
DOI: 10.1177/0049475520945443
|View full text |Cite
|
Sign up to set email alerts
|

Retained biliary plastic stents – lest we forget

Abstract: Prolonged indwelling of endoscopically placed biliary plastic stents may lead to complications. We conducted a retrospective analysis of patients who underwent endoscopic retrograde cholangio-pancreaticography (ERCP) at our centre in 2017 and were noted to have retained biliary plastic stents ( > 3 months after an index ERCP). A total of 127 patients had previously placed biliary plastic stents, out of which 45 (35.4%) were retained. The median age of the latter was 52 years (range = 22–79 years) with 27 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…8 The durations of CBD PS retention in various studies by Chandra and colleagues, Sohn et al, and Jaleel et al was 3.53 years (range 1-14 years), 22.6 AE 12.8 months, and 144 days (94-3,929 days), respectively. 4,5,9 In other studies, it was shown that CBD PS patency ranges from 2.7 to 7 months for benign diseases and from 1.8 to 5.7 months for malignant biliary diseases. [10][11][12][13][14] In our study, the median duration of stent retention was 5 months (IQR ¼ 4-6 months).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 The durations of CBD PS retention in various studies by Chandra and colleagues, Sohn et al, and Jaleel et al was 3.53 years (range 1-14 years), 22.6 AE 12.8 months, and 144 days (94-3,929 days), respectively. 4,5,9 In other studies, it was shown that CBD PS patency ranges from 2.7 to 7 months for benign diseases and from 1.8 to 5.7 months for malignant biliary diseases. [10][11][12][13][14] In our study, the median duration of stent retention was 5 months (IQR ¼ 4-6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the study by Jaleel et al, all patients were managed medically and endoscopically (18/45 patients required further sessions) while Kumar et al reported definitive endoscopic treatment only in 5 patients (23.8%) and necessity of surgical exploration in remaining 16 (76.2%) cases. 4 9 Sohn et al reported successful endoscopic management of retained CBD stent in 35 of 38 patients (92.1%). 5 While most studies have reported > 90% success with endoscopic measure, Chandra and colleagues had lower success which can be attributed to selection and referral bias from a surgical center, lack of technical expertise, and access to various newer accessories and cholangioscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retained biliary stents for a prolonged period without follow up may cause serious, or even life-threatening, complications such as acute cholangitis, pancreatitis, internal stent migration, endoprosthesis occlusion and obstructive jaundice (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In these cases, the mortality rate can reach up to 12% (3).…”
Section: Introductionmentioning
confidence: 99%